Insights into early pathogenesis of sporadic Alzheimer’s disease: role of oxidative stress and loss of synaptic proteins - Ansari, Mubeen A.; Rao, Muddanna Sakkattu; Al-Jarallah, Aishah (Frontiers in Neuroscience, 2024)
Oxidative stress, induced by impaired insulin signaling in the brain contributes to cognitive loss in sporadic Alzheimer's disease (sAD). This study evaluated early hippocampal oxidative stress, pre-and post-synaptic proteins in intraperitoneal (IP) and intracerebroventricular (ICV) streptozotocin (STZ) models of impaired insulin signaling. Adult male Wistar rats were injected with STZ, IP or ICV, and sacrificed 1-, 3-, or 6-weeks post injection. Rat's cognitive behavior was assessed using Morris water maze (MWM) tests at weeks 3 and 6. Hippocampal synaptosomal fractions were examined for oxidative stress markers and presynaptic [synapsin I, synaptophysin, growth-associated protein-43 (GAP-43), synaptosomal-associated protein-25 (SNAP-25)] and postsynaptic [drebrin, synapse-associated protein-97 (SAP-97), postsynaptic density protein-95 (PSD-95)] proteins. IP-STZ and ICV-STZ treatment impaired rat's cognition, decreased the levels of reduced glutathione (GSH) and increased the levels of thiobarbituric acid reactive species (TBARS) in a time dependent manner. In addition, it reduced the expression of pre-and postsynaptic proteins in the hippocampus. The decline in cognition is significantly correlated with the reduction in synaptic proteins in the hippocampus. In conclusion, impaired insulin signaling in the brain is deleterious in causing early synaptosomal oxidative damage and synaptic loss that exacerbates with time and correlates with cognitive impairments. Our data implicates oxidative stress and synaptic protein loss as an early feature of sAD and provides insights into early biochemical and behavioral changes during disease progression.